Highly selective visible light-induced Ti–O bond splitting in an ansa-titanocene dihydroxido complex12. Issue 15 (19th January 2015) - Godemann, Christian; Dura, Laura; Hollmann, Dirk; Grabow, Kathleen; Bentrup, Ursula; Jiao, Haijun; Schulz, Axel; Brückner, Angelika; Beweries, Torsten
Abstract : Visible light irradiation of an ansa -titanocene(iv ) dihydroxido complex Me4 Si2 (C5 Me4 )2 Ti(OH)2 induces highly selective Ti–O bond activation to exclusively yield Ti(iii ) complexes. Abstract : Irradiation of a substituted ansa -titanocene(iv ) dihydroxido complex with visible light induces Ti–O bond dissociation. In contrast to previous studies on structurally similar unbridged complexes, no side reactions are observed and formation of the Ti(iii ) species is highly selective. The formation of OH radicals was proved using a biradicaloid species.